Deskripsi Siklus Menstruasi Pada Wanita Usia Subur dengan Akseptor KB Suntik - Murniasih, Suci; Dwi Aprilina, Happy (Universitas Muhammadiyah Magelang, 2019)
Hormonal contraception with injection the functions in preventing ovulation process. Side effects of contraception such as changes in body weight, menstrual cycle disorders, depression, vaginal discharge and acne.Disorders of menstrual pattern in injectable family planning acceptor such as amenorrhea, bleeding and duration of menstruation.The objective to know the description menstrual cycle on women of childbearing age with injectable family planning acceptorQuantitative research with descriptive approach design.1-month injectable KB acceptors and 3-month injectable KB acceptors in the Puskesmas 1 Sokaraja working area are the population in this study.Purposive sampling as a data retrieval technique and data analysis techniques using univariate.The result is demonstrate that the majority of respondents characteristic of 1 month old KB aged 20-35 years (87,%) Junior high school education (46,6%) not work (75,0%) While KB 3 month age 20-35 years (81,3% ) SMA (51.3%) unemployed (75.0%) based on changing pattern of 1 month non-breastfeeding (65.6%) age of menarche 12 years (40.6%) multiparity parity (46.9%) 1 year (37.5%) Weight gain (84.4%) normal menstrual cycle (59.4%) normal blood count (93.8%) abnormal menstrual period (68.8%) and injecting 3 (56.3%) Â± 1 years of age (34.4%) Weight gain (87.6%) No menstrual cycle (56.3%) Menarche age 11 years (37.5%) normal (100.0%) normal blood count (68.7%) abnormal menstrual period (62.5%).Family planning acceptors injectable with 3 months experience changes in menstruation such as changes in menstrual cycle, menstrual blood count and menstrual period compared to family planning acceptors 1 month injectable.